Концептуальні засади конкурентоспроможного розвитку вітчизняного овочівництва - Кальченко, Сергій Володимирович; Кальченко, Сергей Владимирович; Kalchenko, Serhii (My University, 2017)
UK: В статті розглянуто концептуальні засади конкурентоспроможного розвитку вітчизняного овочівництва. Розкрито специфіку функціонування даної галузі в системі національної економіки. Обґрунтовано необхідність створення умов для ефективного функціонування малих форм аграрного виробництва, а також підвищення рівня їхнього організаційно-інформаційного забезпечення як запоруки конкурентоспроможного функціонування овочівницької галузі. EN: In the article the conceptual basis of a competitive domestic vegetable. The author emphasizes that the activities of small-scale production is only a necessary response to the transformation process that is constantly occurring in the system of national agricultural production. Peasant households only adapt to corresponding changes in the field of organizational, economic and socio-economic relations. The system of relations formed by representatives of big business with state institutions. The corresponding negative practice that emerged in the days of the planned economy model. It deprives when the subjects of small-scale agricultural production sector opportunities to participate in the development of the industry. The specific sexual functioning of this industry in the national economy. The necessity of creating conditions for the effective functioning of small forms of agricultural production and enhance their organizational and information support as a prerequisite for the functioning of a competitive industry. The author formulated the basic concept of competitive domestic vegetable. The strategy of private households should be on the following principles. 1. Ensuring work family forms functioning of the economy as a basic component of rural development. 2. Promote the transition peasant households in agricultural commodity bases with providing simultaneous diversification of economic activities at the village. 3. Active involvement of private farms to a system of domestic agricultural production as subjects of economic relations by establishing cooperative associations. 4. Training for private households to provide mass transfer of small-scale agricultural business sector to a new level of functioning and development of rural areas.
Conceptual foundations competitive development of the domestic vegetable growing
Keywords: овочівництво; селянські домогосподарства; конкурентоспроможність; інформаційне забезпечення; vegetable; peasant households; competitiveness; information